2010
DOI: 10.1007/s10530-010-9887-4
|View full text |Cite
|
Sign up to set email alerts
|

Could poor seed dispersal contribute to predation by introduced rodents in a Hawaiian dry forest?

Abstract: Dry forests are among the most diverse, yet threatened, communities in Hawai'i. Dry forests throughout the archipelago suffer from a lack of natural regeneration of trees. Two factors that may limit tree recruitment include poor seed dispersal and seed predation by rodents. Poor or limited dispersal of fleshy-fruited species results in seeds and fruits falling directly under parents. Dispersed and nondispersed seeds may differ in their vulnerability to predation. We tested effects of seed location (under/ away… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 76 publications
2
28
0
1
Order By: Relevance
“…Six of the 12 species had the majority ([50 %) of their fruit removed in treatments that were accessible to rats, and motion-sensing cameras also recorded only black rats removing fruit. Additional recent studies demonstrating post-dispersal fruit removal by invasive rodents have been conducted elsewhere in Hawaii (Chimera and Drake 2011) and in New Zealand (Moles and Drake 1999;Grant-Hoffman et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the 12 species had the majority ([50 %) of their fruit removed in treatments that were accessible to rats, and motion-sensing cameras also recorded only black rats removing fruit. Additional recent studies demonstrating post-dispersal fruit removal by invasive rodents have been conducted elsewhere in Hawaii (Chimera and Drake 2011) and in New Zealand (Moles and Drake 1999;Grant-Hoffman et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents may also directly influence plants through the consumption of vegetative and reproductive parts (Sugihara 1997;McConkey et al 2003;Salvande et al 2006;Grant-Hoffman and Barboza 2010;Shiels 2011). As seed predators (see Grant-Hoffman and Barboza 2010 for a review), invasive rodents have been implicated in the breakdown of reproductive cycles of numerous island plant species (Campbell and Atkinson 2002;Meyer and Butaud 2009;Auld et al 2010;Chimera and Drake 2011;Shiels and Drake 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamashita et al (2003) suggested that R. rattus may be facilitating the invasion of the nonnative tree Bischofia javanica in the Ogasawara Islands because R. rattus depredates the seeds of the dominant native tree Elaeocarpus photiniae-folius both before dispersal (27% -33% of the seed crop) and after dispersal (41% -100%). Several other studies of fruit and seed removal have occurred on Pacific islands that include R. rattus as part of the rodent community, but the particular rodent species responsible for such removals were not identified (e.g., Moles and Drake 1999, Uowolo and Denslow 2008, Meyer and Butaud 2009, Erwin and Young 2010, GrantHoffman et al 2010, Chimera and Drake 2011.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
“…Rattus rattus does not seem to be limited by an upper temperature level, or at least this has not been investigated. Thus, R. rattus is abundant and spans most terrestrial communities, from arid lowland and montane ecosystems (Tamarin and Malecha 1971, Clark 1981, Amarasekare 1994, Harris and Macdonald 2007, Chimera and Drake 2011 to lowland and montane rain forests (Daniel 1973, Sugihara 1997, Lindsey et al 1999, Wegmann 2009). Even in highly disturbed environments, such as Eniwetok Atoll, which suffered numerous nuclear explosions, R. rattus survived in densities of approximately 20 individuals/ ha 10 yr after the last nuclear test (Fall et al 1971).…”
Section: Climate Requirements Limitations and Ecosystems Invadedmentioning
confidence: 99%